Harmoni dalam Perbedaan: Toleransi Antarumat Beragama di Desa Tebel, Bareng - Muh. Ikhsan Nurdin; Muh. Atmim Nurona; Muh. Syukrur Rizki; Azzaida Naura Amalia; Rohmatul Lailiyah; Taufiqur Rohmah; Iva Inayatul Ilahiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Tebel Bareng Village is a clear example of how religious differences do not have to be an obstacle to social harmony. Through This research explores local cultural values through an ethnographic approach. that foster interfaith tolerance. The tradition of gotong royong and deliberation are key to maintaining harmonious social relations.The results demonstrate that local culture plays a pivotal role in instilling tolerance values into people's daily lives.These villagers prove that Different beliefs are not walls of separation but bridges that allow people to get to know each other.appreciate each other. This research describes inspiring stories from daily life where religious people help each other regardless of background. beliefs. Using a narrative qualitative approach, the study presents a vivid and inspiring portrait of tolerance and offering hope that Harmony can be achieved in a pluralistic society.